Femoral Neurogram Before Transpsoas Spinal Access at L4–5 Intervertebral Disk Space: A Proposed Screening Tool. Issue 7 (August 2015) - Davis, Timothy T.; Day, Thomas F.; Bae, Hyun W.; Rasouli, Alexandre
Abstract : Study Design: Observational study. Objective: To illustrate the variability of the course of the femoral nerve across the L4–5 disk space, and to present a novel application of transforaminal epidural steroid injections (TFESI) in the visualization of femoral nerve roots. Summary of Background Data: A concern regarding the lateral retroperitoneal transpsoas approach is the proximity of the lumbar plexus. Current techniques of assessing the proximity of neural tissue to the L4–5 disk space have limited capabilities. Methods: A total of 100 patients were selected for L4–5 TFESI (L4 selective nerve root blocks) because of lumbar radiculopathy. L4 neurograms were obtained while performing L4–5 TFESI under flouroscopic guidance, using a retroneural technique. The course of the L4 root/femoral nerve was then evaluated under fluoroscopy in the anteroposterior and lateral planes. Images were then reviewed by a radiologist, physiatrist, and 2 orthopedic spine surgeons. Results: Fluoroscopic evaluation revealed that the pattern of location of the femoral nerve was highly variable. In males, it was located 4.7% in zone 2, 32.5% in zone 3, 53.5% in zone 4, and 9.3% in zone P. In female patients, it was located 7.0% in zone 2, 14% in zone 3, 54.4% in zone 4, and 24.6% in zone P. Conclusions: An L4 neurogram will provide an accurate trajectory of L4 root/femoral nerve as it crosses the L4–5 intervertebral disk space. An accurate assessment is essential to help minimize the increasing frequency of thigh pain, paresthesias, and weakness associated with the lateral access to the L4–5 intervertebral disk space. Femoral nerves that fall within zones 2 and 3 will require more manipulation during retraction and may be better suited with a different surgical approach.